Pengaruh Filsafat Ketuhanan Ronggowarsito Terhadap Kepercayaan Masyarakat di Jawa - Della, Dian Annisa Rizkyah Wati (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This study explains Roggowarsito's thoughts about divine philosophy and its relation or influence on the beliefs of the Javanese people or commonly known as kejawen. This study uses the library research method. namely a research that focuses on literary discussions. Sources of data used in this study are primary and secondary sources. After collecting both primary and secondary data sources, the next step is to analyze it using the content analysis method. This method is used to analyze the extent to which the teachings of Raden Ngabehi Ronggowarsito's philosophy of God in his Wirid Hidayat Jati Fiber and its influence on spirituality the sect of Kebatinan (Kejawen). As well as using a philosophical historical-normative research approach, is to analyze Raden Ngabehi Ronggowarsito's thoughts by exploring the biography and activities carried out by Raden Ngabehi Ronggowarsito to find out the background of his thoughts and the philosophical framework he uses related to the teachings of God.